The ESSENTIAL MIDWIFERY CARE FOR MRS. M DURING PREGNANCY, LABOUR, POSTPARTUM, AND NEONATAL CARE AT KERTAMUKTI COMMUNITY HEALTH CENTER, CILEBAR DISTRICT, KARAWANG REGENCY IN 2026 - Irma Yanti (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Pregnancy, labour, postpartum, and neonatal periods are physiological phases with the potential for complications that increase maternal and neonatal mortality risks. This report aims to provide and document essential midwifery care for a pregnant, laboring, and postpartum mother, as well as her newborn. This report employs essential midwifery care management utilizing Varney’s seven-step approach, documented in the SOAP format. Data were collected through interviews, physical examinations, observations, and documentation reviews of the Kesehatan Ibu dan Anak (KIA/Maternal and Child Health) handbook. The implementation of essential midwifery care management for Mrs. M commenced at 32 weeks of gestation. During the antenatal period, four antenatal care (ANC) visits were conducted between 32 and 37 weeks of gestation. The assessment revealed mild anemia and proteinuria (+). During delivery, the patient sustained a second-degree perineal laceration, and Early Initiation of Breastfeeding (EIBF) lasted less than one hour. It is anticipated that the identified gaps between theory and clinical practice will optimize future care delivery, and that the client and her family will adhere to the health education provided by healthcare professionals.